Genetic differentiation between two dairy type river buffalo breeds (Bubalus bubalis) of North India using microsatellite markers: - P Kathiravan; RS Kataria; SS Bulandi; DK Sadana; BP Mishra (Journal of Livestock Biodiversity, 2025)
The present study was undertaken with the objective of investigating the genetic structure of Nili-Ravi and Murrah buffaloes, the two important dairy type river buffalo breeds of North India. A total of 95 animals representing Nili-Ravi and Murrah buffaloes were analyzed using 24 heterologous cattle microsateliite markers which revealed an average of 5.28 and 5.16 alleles per locus respectively. The average inbreeding coefficient (F15) was substantially high in both Nili-Ravi and Murrah buffaloes, with significant deficit of heterozygotes viz. 18.8% and 22.8% respectively. The test for Hardy-Weinberg equilibrium showed significant deviations at most of the loci in both the populations except 9 in Nili-Ravi and 8 in Murrah buffaloes respectively. The mean multilocus FsT value (0.124) suggested significant (P<0.01) degree of breed differentiation. The Neighbour-Joining tree constructed from allele sharing distance measures among individual animals showed two distinct clusters of the two breeds. Principal component analysis supported this genetic differentiation as the scatter diagram revealed distinct clustering of individuals of these two breeds. Bayesian cluster analysis also revealed a similar type of genetic structure, with the proportion of membership coefficient in each of the two inferred populations being more than 98% from either of the two source population respectively. The genetic distinctness of these two north Indian dairy type buffalo breeds as revealed by microsatellite analysis may have significant impact on issues concerning conservation and biodiversity.